If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(7x-9)+(6x+8)=90
We move all terms to the left:
(7x-9)+(6x+8)-(90)=0
We get rid of parentheses
7x+6x-9+8-90=0
We add all the numbers together, and all the variables
13x-91=0
We move all terms containing x to the left, all other terms to the right
13x=91
x=91/13
x=7
| -11x+7(x-10)=42 | | -6-6x=5x-50 | | -10h+4=-3h-10 | | -3(-9x+9)-9x=2(x-5)-9 | | Y^2-33+2y=0 | | 2f=f+10 | | 10-b=-3b | | -4h=6-3h | | 1.9x1.9=3.61 | | 5x+555=10655 | | 5x=25^-2x-5 | | 4+2x=-7x+58 | | -3x+1=1+2x | | 5x-10=7x+-4 | | -4x+8-3x+1=0 | | 2x+30+x+3x-30=180° | | -x-1=-13+2x | | 52x+2=125 | | 3/5=1/3r | | -11=3+4x | | 6u=4u+10 | | 6.8=d+4.1 | | 3/5/r=1/3 | | 5x-2+x=93x+10 | | 10^(x–4)=100 | | 3y+33=9(y+1) | | 3x+-1=2x+6 | | -6u+3(u+7)=33 | | x+613=2 | | 8n-3=5n+9 | | -2(x-1)=-4x+12 | | 3.5=c-12 |